Preparation of Plasmid λdv from Bacteriophage λ: Role of Promoter-Operator in the Plasmid Replicon - Matsubara, Kenichi (1974)
A technique has been described for selection of bacteria carrying plasmid λdv. With this technique, the effects of mutations in the promoter-operators were compared on the production and perpetuation of the plasmid. It was found that “left” promoter-operator that controls leftward gene expressions can be deleted from the plasmid genome. Some mutations of “right” promoter-operator (pRoR) that controls expression of genes tof, O, and P affect the stability of the plasmid. However, the plasmid genome accomodates a variety of pRoR mutations within a reasonable but different degree of constitutivity. Some new promoter mutations that allow bypass of the pRoR cannot be carried in the plasmid genome. From these findings it was proposed that the plasmid replicon has one indispensable promoter-operator that controls expression of all the genes related to its own replication, although a variety of constitutive mutations can be accommodated in the pRorR.